IMPLEMENTASI DISIPLIN KERJA UNTUK MENINGKATKAN KIENERJA KARYAWAN PADA PT. MITRA LONDRI SUKSES DI TANGERANG - Dwi Khumaira, Anne; Suryani, N. Lilis (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study employs a descriptive qualitative approach using observation, interviews, and documentation methods This study examines the implementation of work discipline and its effectiveness in improving employee performance at PT Mitra Londri Sukses in Tangerang. Based on initial observations, indications of a lack of employee discipline were found, impacting production and delivery delays, as well as irregular absenteeism. This research employs a descriptive qualitative approach using observation, interviews, and documentation methods. Research informants include the General Manager, Supervisor, and two Production Staff. The results show that PT Mitra Londri Sukses implements work discipline through a corrective approach, which includes advice, verbal warnings, warning letters, and even termination of employment, adjusted to the severity of the violation (minor, moderate, severe). These efforts aim to control work and improve employee attitudes, fostering a sense of responsibility and professionalism. Although the effectiveness of work discipline implementation has not yet reached 100% (currently around 85% compliance rate), the company consistently conducts coaching, rule socialization, and periodic evaluations. This implementation of work discipline has proven to have a positive impact on increasing employee productivity and customer satisfaction, reflected in faster and more punctual laundry services Keywords: Work Dicipline, Employee Performance. PT Mitra Londri Sukses